2012
DOI: 10.1007/s11033-012-1893-4
|View full text |Cite
|
Sign up to set email alerts
|

Study of the association between glutathione S-transferase (GSTM1, GSTT1, GSTP1) polymorphisms with type II diabetes mellitus in southern of Iran

Abstract: Diabetes Mellitus is characterized by chronic hyperglycemia and associated with an increased production of reactive oxygen species (ROS). Oxidative stress is the result of accumulation of free radicals in tissues which specially affects beta cells in pancreas. Glutathione S-transferases (GSTs) are a family of antioxidant enzymes that include several classes of GSTs. These enzymes have important roles in decreasing of ROS species and act as a kind of antioxidant defense. To investigate the association between G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 32 publications
5
43
2
1
Order By: Relevance
“…[60] In a related perspective, the use of GT activity as a reliable biomarker in depicting the etiology of diabetes mellitus has been described. [2] It was posited that two isoforms of GST (GSTM1 and GSTT1) might be involved in the pathogenesis of Type 2 diabetes mellitus in a South Iranian population. In addition, investigations have shown that the GSTM1 gene may play a significant role in the aetiopathogeneses of diabetes mellitus and could serve as a useful biomarker in the prediction of diabetes mellitus susceptibility of the Turkish population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[60] In a related perspective, the use of GT activity as a reliable biomarker in depicting the etiology of diabetes mellitus has been described. [2] It was posited that two isoforms of GST (GSTM1 and GSTT1) might be involved in the pathogenesis of Type 2 diabetes mellitus in a South Iranian population. In addition, investigations have shown that the GSTM1 gene may play a significant role in the aetiopathogeneses of diabetes mellitus and could serve as a useful biomarker in the prediction of diabetes mellitus susceptibility of the Turkish population.…”
Section: Discussionmentioning
confidence: 99%
“…Primarily, overall physiologic distortions prompted by poor control of metabolism in the absence or insufficiency of insulin engender hyperglycemia and associated metabolic disorders. [1,2] Striking consequential effects of prolonged hyperglycemia include changes in the structure and function of macromolecules, [3,4] auto-oxidation of glycated proteins, increased production of reactive oxygen species (ROS), decreased antioxidant defense, increased lipid peroxidation, and associated apoptosis or necrosis occasioned by membrane degeneration. [4,5] Notably, alterations/adjustments in most glycolytic and tricarboxylic acid cycle (TCA) enzyme activities are associated with diabetic states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Restriction fragment length polymorphism-polymerase chain reaction (PCR) and multiplex PCR methods were used to determine the genotype of the GST gene in each sample (Table 1). 26,27 restriction fragment length polymorphism and multiplex Pcr techniques GSTM1 and GSTT1 genetic polymorphisms were determined using a multiplex PCR technique. Polymerase chain reaction amplification for the GSTM1 and GSTT1 locus was performed using an initial denaturation step at 94°C for 2 minutes, followed by denaturation at 94°C for 2 minutes, annealing at 64°C for 1 minute, an extension step at 72°C for 1 minute in 35 cycles, and a final extension step at 72°C for 10 minutes.…”
Section: Dna Extractionmentioning
confidence: 99%
“…The primers for the PCR studies are summarized in Table 1. 26,27 Statistical analyses Descriptive analyses were reported as frequencies. Quantitative variables were expressed as means ± standard deviation.…”
Section: Dna Extractionmentioning
confidence: 99%